Images of Mind, Images of God Mirror as Metaphor in Chinese Buddhism and Early Mysticism - Fan, Jiani (Buddhist Christian studies, 2018)
In ancient China, Zen Buddhism undergoes three stages of transformation: from advocating "contemplating the heart" and "maintaining quiet," into "absence of thought" and "see one's nature," then into "ordinary mind is the way," which corresponds to Meister Eckhart's three stages concerning the relation between human beings and God: man created according to the image of God, man as creature flowing out of the God of nothingness, and detachment from the concept of God. In this article, we will discuss the mirror as an indispensable metaphor in the process of Zen Buddhism's and German Mysticism's transformation, as a mediator between man and God, sometimes even discarded as an obstacle to discern Godhead as nothingness or to act in quotidian life with a detached ordinary mind. The essay will discuss the different functions of mirror image in Mysticism and Zen Buddhism, and how the apophatic approach facilitates pure mystic experience to access the non-embodied or even Godhead reduced to nothingness, as well as Buddha-nature, through "'emptying' out of other conscious content in order to 'make room' for the apprehension of God, who is beyond our discursive, sensual natures." Therefore, nothing and nobody, through apophasis, should replace Him and God, which not only is discussed in Meister Eckhart's later sermons, but also is unfolding in the conflict between two eminent ancient Chinese Zen masters, Huineng (the Sixth Patriarch) and Shenxiu. The "ordinary mind is the way" in Zen Buddhism, resonating profoundly with Mystic detachment, indicates the different emphasis on vita contemplativa and vita activa in different periods, as well as diverting beings gradually from attachment to the heart and divinity to leading a spontaneous life guided by detachment and ordinary mind.